The Last Nomadic Tribe of Nepal: The Rautes - Adhikari, Sunika; Kharki, Reena (KDCBAR Law Journal, 2025)
Nepal is often associated with a series of snow-capped mountains and the revered birthplace of Lord Gautam Buddha. However, it cannot be denied that the country welcomes visits from the ‘unknown’ to partake in the infinite spectrum of cultures, languages, and customs. Among these, the Raute—a small and marginalized group of hunter-gatherers—stand out as the last remaining nomadic tribe in Nepal. The Raute, believed to be a part of the Khas Aryas group, have lived a reclusive existence in the forests of the Karnali, Dailekh, and Surkhet provinces for centuries. The issue is further exacerbated by a threat to their civilization and well-being. Their way of life, guided by three core principles—no settlements, no agriculture, and no formal education—is now under significant threat due to the rapid escalation of crony capitalism and modernization. Today, fewer than 150 of them remain as the final vestiges of a 900-year-old folklore of “eccentric nomadic barbarisms”; a derogatory term used by the civil societies. Thus, the government of Nepal considers their way of life as some wildly romantic existence living cheek-by-jowl with nature, yet compels them to give up the norm and gradually conform towards the ‘mainstream’, regardless of how ‘xenophobic’ the nomads feel. This paper examines the complex challenges facing the Raute, including their social, economic, and political dynamics, and critically analyzes the role of the Nepali government and other external actors. It argues that a deeper understanding of the Raute's cultural resilience and their deep-seated xenophobia is essential for developing effective conservation policies that respect their right to self-determination and preserve their unique heritage.